Solving stiff ordinary differential equations using extended block backward differentiation formulae. - Mohd Yatim, Siti Ainor; Ibrahim, Zarina Bibi; Othman, Khairil Iskandar; Suleiman, Mohamed (Springer, 2013)
A comprehensive research on the existing Block Backward Differentiation Formulae (BBDF) was done. Based on the suitability in solving stiff ordinary differential equations (ODEs), BBDF of order 3 up 5 is collected using simplified strategy in controlling the step size and order of the method. Thus, Extended Block Backward Differentiation Formulae (EBBDF) is derived with the intention of optimizing the performance in terms of precision and computation time. The accuracy of the method are investigated using linear and non linear stiff initial value problems and its performance is compared with MATLAB’s suite of ODEs solvers namely ode15s and ode23s.